2018
DOI: 10.1080/10717544.2018.1446475
|View full text |Cite
|
Sign up to set email alerts
|

Eph A10-modified pH-sensitive liposomes loaded with novel triphenylphosphine–docetaxel conjugate possess hierarchical targetability and sufficient antitumor effect both in vitro and in vivo

Abstract: Mitochondrial-targeting therapy was considered to be a promising approach for the efficient treatment of cancer while positive charge induced nonspecific cytotoxicity severely limits its application. To overcome this drawback, a novel mitochondria targeted conjugate triphenylphosphine-docetaxel (TD) has been synthesized successfully and incorporated it into liposomes (EPSLP/TD), which possessed excellent pH-sensitive characteristic, EphA 10 mediated active targetability as well as mitochondria-targeting capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 52 publications
(59 reference statements)
0
22
0
Order By: Relevance
“…To our knowledge, this is the first report to demonstrate that levels of EphA10 positively correlate with the tumorigenic potential of pancreatic cancer cells both in vitro and in vivo. EphA10 has been identified as a therapeutic target in breast and prostate cancers, and neutralizing monoclonal antibodies to EphA10 as well as EphA10 antibody‐drug conjugates have been developed 10,11,14,38,39 . Our results suggested that EphA10 may be a valuable therapeutic target to treat refractory pancreatic cancer and other cancers that are positive for EphA10 expression.…”
Section: Discussionmentioning
confidence: 68%
“…To our knowledge, this is the first report to demonstrate that levels of EphA10 positively correlate with the tumorigenic potential of pancreatic cancer cells both in vitro and in vivo. EphA10 has been identified as a therapeutic target in breast and prostate cancers, and neutralizing monoclonal antibodies to EphA10 as well as EphA10 antibody‐drug conjugates have been developed 10,11,14,38,39 . Our results suggested that EphA10 may be a valuable therapeutic target to treat refractory pancreatic cancer and other cancers that are positive for EphA10 expression.…”
Section: Discussionmentioning
confidence: 68%
“…When micelles are incorporated with hydrophobic therapeutic agents, the solubility problems are solved [84]. Liposomes are compatible with the cell membrane and thus the most popular carriers for cell endocytosis [85, 86]. Polymers could incorporate both hydrophilic and hydrophobic agents to increase solubility [87, 88].…”
Section: Nanoparticles As Vehicles For Gene Deliverymentioning
confidence: 99%
“… pH Polymer-drug conjugates DOX 4T1 Endocytosis pathway Lysosome & mitochondria 1.9-fold higher 2.5-fold lower Yes (Cas-3 activation) [ 81 ] Eph A10/TPP-DTX liposomes Docetaxel MCF-7 EphA 10 receptor mediated cell endocytosis Mitochondria 0.14-fold lower Lower IC 50 value Yes (highest Cas-3 and Cas-9 expression) [ 42 ] CTPP-CSOSA/celastrol micelles Celastrol MCF-7 Endocytosis pathway Mitochondria Dropped dramatically Lower IC 50 value Yes (obvious increase in Cas-3 and Cas-9 activity) [ 43 ] HER-2/DOX DQAsomes DOX MCF-7 and MCF-7/ADR HER-2 peptide-mediated endocytosis Mitochondria A 6.9% decrease 2.6-fold lower Yes (activated Cas-3 and Cas-9) [ 36 ] PEG-AIE-TPP micelle AIE-TPP MCF-7 Endocytosis pathway Mitochondria Yes [ 44 ] HPMA-MSN/DTX nanoparticles Docetaxel HeLa Endocytosis pathway Mitochondria Collapse A lower IC 50 compared to pH7.4 …”
Section: Introductionmentioning
confidence: 99%